Characterization of Platinum and Iridium Oxyhydrate Surface Layers from Platinum and Iridium Foils. Issue 13 (25th May 2016) - Johnson, Benjamin; Ranjan, Chinmoy; Greiner, Mark; Arrigo, Rosa; Schuster, Manfred Erwin; Höpfner, Britta; Gorgoi, Mihaela; Lauermann, Iver; Willinger, Marc; Knop‐Gericke, Axel; Schlögl, Robert
Abstract: Platinum and iridium polycrystalline foils were oxidized electrochemically through anodization to create thin platinum and iridium hydrous oxide layers, which were analyzed through laboratory photoelectron spectroscopy during heating and time series (temperature‐programmed spectroscopy). The films contain oxygen in the form of bound oxides, water, and hydroxides and were investigated by depth profiling with high‐energy photoelectron spectroscopy. The Pt films are unstable and begin to degrade immediately after removal from the electrolyte to form core–shell structures with a metallic inner core and a hydrous oxide outer shell almost devoid of Pt. However, evidence was found for metastable intermediate states of degradation; therefore, it may be possible to manufacture PtO x phases with increased stability. Heating the film to even 100 °C causes accelerated degradation, which shows that stoichiometric oxides such as PtO2 or PtO are not the active species in the electrolyte. The Ir films exhibit increased stability and higher surface Ir content, and gentle heating at low temperatures leads to a decrease in defect density. Although both layers are based on noble metals, their surface structures are markedly different. The complexity of such hydrous oxide systems is discussed in detail with the goal of identifying the film composition more precisely. Abstract : Oxidized foils : Platinum and iridium polycrystalline foils are oxidized electrochemically through anodization to create thin platinum and iridium hydrous oxide layers, which are analyzed through X‐ray photoelectron spectroscopy. The complexity of such hydrous oxide systems is discussed in detail.